Adaptation to a low carbohydrate high fat diet is rapid but impairs endurance exercise metabolism and performance despite enhanced glycogen availability - Burke, L. M.; Whitfield, J.; Heikura, I. A.; Ross, M. L. R.; Tee, N.; Forbes, S. F.; Hall, R.; McKay, A. K. A.; Wallett, A. M.; Sharma, A. P. (The Journal of Physiology, 2020)
Key points Brief (5-6 days) adaptation to a low carbohydrate high fat diet in elite athletes increased exercise fat oxidation to rates previously observed with medium (3-4 weeks) or chronic (>12 months) adherence to this diet, with metabolic changes being washed out in a similar time frame. Increased fat utilisation during exercise was associated with a 5-8% increase in oxygen cost at speeds related to Olympic Programme races. Acute restoration of endogenous carbohydrate (CHO) availability (24 h high CHO diet, pre-raceCHO)only partially restored substrate utilisation during a race warm-up. Fat oxidation continued to be elevated above baseline values although it was lower than achieved by 5-6 days` keto adaptation; CHO oxidation only reached 61% and 78% of values previously seen at exercise intensities related to race events. Acute restoration of CHO availability failed to overturn the impairment of high-intensity endurance performance previously associated with low carbohydrate high fat adaptation, potentially due to the blunted capacity for CHO oxidation.